2022
DOI: 10.1021/acsami.1c18495
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Stretchable Block Copolymer Based on PEDOT:PSS for Improved Performance in Bioelectronic Applications

Abstract: The conductive polyelectrolyte complex poly­(3,4-ethylenedioxythiophene):poly­(styrenesulfonate) (PEDOT:PSS) is ubiquitous in research dealing with organic electronic devices (e.g., solar cells, wearable and implantable sensors, and electrochemical transistors). In many bioelectronic applications, the applicability of commercially available formulations of PEDOT:PSS (e.g., Clevios) is limited by its poor mechanical properties. Additives can be used to increase the compliance but pose a risk of leaching, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 73 publications
0
37
0
Order By: Relevance
“…[46][47][48] A PEG-based crosslinker was selected as the new crosslinker because of its flexibility, which has been incorporated into mixed conductors to improve flexibility. [49][50][51] Some studies have employed PEGDE as a flexible crosslinker for the polymer films of PEDOT: PSS. [52][53][54] Structural analysis revealed that PNIPAM was segregated on the surface and that the PEGDE crosslinker increased the crystallinity of PEDOT.…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48] A PEG-based crosslinker was selected as the new crosslinker because of its flexibility, which has been incorporated into mixed conductors to improve flexibility. [49][50][51] Some studies have employed PEGDE as a flexible crosslinker for the polymer films of PEDOT: PSS. [52][53][54] Structural analysis revealed that PNIPAM was segregated on the surface and that the PEGDE crosslinker increased the crystallinity of PEDOT.…”
Section: Introductionmentioning
confidence: 99%
“…The sEMG electrodes were made using PEDOT:PSS (1) -b-PPEGMEA (6) block copolymer ("Block-6") designed and synthesized with electrical and mechanical properties tuned for measuring electromyography signals on-body (Figure 2). [60] PEDOT:PSS is a conductive polymer used in many different fields of electronics due to its high conductivity with additives and its molecular stability. [61][62][63][64][65] However, the additives used to increase the stretchability and the conductivity tend to be toxic and can leach out over time decreasing the performance of the polymer.…”
Section: Conductive Polymer-based Semg Sensormentioning
confidence: 99%
“…The mechanical properties of the PEDOT:PSS layer also likely contributed to this observed debonding behavior. P3BT was the only polymer in the series to have an elastic modulus greater than PEDOT:PSS (∼385 MPa), which likely prevented crazing at the PEDOT:PSS/P3BT interface due to elastic mismatch. In contrast, n = 5–7 all delaminated at the PEDOT:PSS/P3AT interface with low measured peel forces (∼60 N m –1 ), which is consistent with findings from the Dauskardt group showing that the PEDOT:PSS/P3HT:PCBM interface is weakest within a device stack. , At n = 8, there was a transition at which the adhesion between the P3AT/tape interface became weak enough such that it becomes the most favorable debonding interface.…”
Section: Resultsmentioning
confidence: 99%